2021
DOI: 10.1080/23311975.2021.1938930
|View full text |Cite
|
Sign up to set email alerts
|

Assessing SMEs tax non-compliance behaviour in Sub-Saharan Africa (SSA): An insight from Nigeria

Abstract: The existing studies on determinants of small and medium enterprises (SMEs) tax compliance behaviour in Sub-Saharan Africa have been criticised on account of limited study scope which compromises generalisation and poor theorisation that have little or no support for the research questions of such studies. The current study is rooted in behavioural economics theory and elicits information from 392 participants from all geopolitical zones of Nigeria using paper-and-pencil survey instruments. The study's finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 56 publications
1
42
0
1
Order By: Relevance
“…In the past few decades, tax researchers have increased their efforts to better understand issues such as tax compliance behavior, tax morale, and tax evasion. Their findings support the theory of behavioral economics as a theoretical framework (Vincent, 2021). According to this line of research, various economic and behavioral factors affect tax compliance decisions.…”
Section: Literature Reviewsupporting
confidence: 75%
See 1 more Smart Citation
“…In the past few decades, tax researchers have increased their efforts to better understand issues such as tax compliance behavior, tax morale, and tax evasion. Their findings support the theory of behavioral economics as a theoretical framework (Vincent, 2021). According to this line of research, various economic and behavioral factors affect tax compliance decisions.…”
Section: Literature Reviewsupporting
confidence: 75%
“…According to this line of research, various economic and behavioral factors affect tax compliance decisions. The economic components of behavioral economics theory highlight the taxpayers’ predisposition toward non-compliance when the estimated gains outweigh the costs (Vincent, 2021). Coercive measures may be used as tools for driving taxpayers to exercise compliant behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have focused their analyses on tax compliance among SMEs [21][22][23][24][25][26][27] and shown that tax compliance costs depend on the age of the firm, location and business activity. Furthermore, tax compliance behaviour is positively related to tax fairness, peer influence and political instability [28,29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Timothy and Abbas (2021) [24], considering a sample of Indonesian SMEs, found that SMEs' tax compliance is positively related to their trust in public authorities but also the level of tax morality and their perception of justice. Considering SMEs from Nigeria, Vincent (2021) [25] revealed that several economic and behavioural factors determine tax compliance behaviour and also that tax information can be seen as one of the main drivers of tax compliance. Further, Wadesango et al (2020) [26] analysed the relationship between tax amnesty and tax compliance among SMEs in Zimbabwe and obtained an inverse relation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Governments around the world have the main goal of reducing the "tax gap", this depends on increasing taxpayer understanding as a driver of tax compliance and the effectiveness of compliance costs (Kwarto & Yunaenah, 2019;Neve & Imbert, 2019). So far, tax compliance has been a hope in various countries for that preparation of tax compliance must be done early by providing tax information to all citizens, tax information is one of the drivers of tax compliance (Vincent, 2021), trust in tax authorities (Batrancea et al, 2019;Gobena & Van Dijke, 2016;Kogler et al, 2013), and education…”
Section: Introductionmentioning
confidence: 99%